آداب قراءة القرآن الكريم - دراسة فقهية - Reading etiquettes of the holy Quran - A study of jurisprudence - Jamalludin Helmi, Hashim; Mohamed Fathy, Mohamed Abdelgelil; Abdullah Mahdi, Jabal (2019)
Remember the Etiquettes of reading the Holy Quran often when mentioning the recitation and so for its virtue and martyrdom to be polite with the Koran when reading, In this research we have collected most of these miscellaneous Etiquettes and mentioned some of the conditions with citing the jurisprudence and the correct evidence in the books of jurisprudence and scientific research, which is difficult to find in one book or one search and some of these conditions : The hearted conditions and we mean potential, including: repentance, sincerity, intention and presence of the heart, and the apparent conditions such as purity and its provisions and abstinence. And for reading there are Etiquettes, including: understanding, reverence, and contemplation, and the covenant of the Koran, respect and magnification, Basmalah and others. In this research we have adopted the explanatory approach, the inductive approach, and the analytical method. The most important results of this research are that the conditions and ethics of reading the Holy Quran have a close connection to the jurisprudential provisions, including what is duty and what is desirable and delegate to it.